Using Publicly Available Data to Construct a Transparent Measure of Health Care Value: A Method and Initial Results. Issue 2 (June 2016) - WEEKS, WILLIAM B.; KOTZBAUER, GREGORY R.; WEINSTEIN, JAMES N.
Abstract : Policy Points : Using publicly available Hospital Compare and Medicare data, we found a substantial range of hospital‐level performance on quality, expenditure, and value measures for 4 common reasons for admission. Hospitals' ability to consistently deliver high‐quality, low‐cost care varied across the different reasons for admission. With the exception of coronary artery bypass grafting, hospitals that provided the highest‐value care had more beds and a larger average daily census than those providing the lowest‐value care. Transparent data like those we present can empower patients to compare hospital performance, make better‐informed treatment decisions, and decide where to obtain care for particular health care problems. Context: In the United States, the transition from volume to value dominates discussions of health care reform. While shared decision making might help patients determine whether to get care, transparency in procedure‐ and hospital‐specific value measures would help them determine where to get care. Methods: Using Hospital Compare and Medicare expenditure data, we constructed a hospital‐level measure of value from a numerator composed of quality‐of‐care measures (satisfaction, use of timely and effective care, and avoidance of harms) and a denominator composed of risk‐adjusted 30‐day episode‐of‐care expenditures for acute myocardial infarction (1, 900 hospitals), coronary artery bypass grafting (884 hospitals), colectomy (1, 252 hospitals), and hip replacement surgery (1, 243 hospitals). Findings: We found substantial variation in aggregate measures of quality, cost, and value at the hospital level. Value calculation provided additional richness when compared to assessment based on quality or cost alone: about 50% of hospitals in an extreme quality‐ (and about 65% more in an extreme cost‐) quintile were in the same extreme value quintile. With the exception of coronary artery bypass grafting, higher‐value hospitals were larger and had a higher average daily census than lower‐value hospitals, but were no more likely to be accredited by the Joint Commission or to have a residency program accredited by the American Council of Graduate Medical Education. Conclusions: While future efforts to compose value measures will certainly be modified and expanded to examine other reasons for admission, the construct that we present could allow patients to transparently compare procedure‐ and hospital‐specific quality, spending, and value and empower them to decide where to obtain care.